Empati dan Kecerdasan Emosi Perannya terhadap Sikap Memaafkan Wanita yang Mengalami Pelecehan Seksual - Safriati, Christine; Rahayu, Anizar; Sovitriana, Rilla (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2022)
This research is motivated by many women who have sexual experiences. The purpose of this study was to determine the significant role of empathy and emotional intelligence on forgiveness of women who have experienced sexual harassment. This study uses three variables, namely empathy, emotional intelligence, and forgiveness. The population in this study are women who have experienced sexual harassment who live in JABODETABEK. The sample taken in this study amounted to 160 people, with incidental sampling. The data collection method uses a Likert model scale, consisting of a forgiveness scale, an empathy scale, and emotional intelligence. The results of the validity test of forgiveness found 21 valid items with very high reliability, 19 valid empathy items with very high reliability, and 25 valid emotional intelligence items with very high reliability. The results of this study obtained Bx1y = 0.275 and a significance level of p: 0.000 (p<0.005), meaning that there is a significant positive role of the empathy variable on the attitude of forgiving women who experience sexual harassment. The results of the analysis Bx2y = 0.303 and a significance level of p: 0.000 (p<0.005), meaning that there is a significant positive role for emotional intelligence variables on forgiveness of women who experience sexual harassment. Obtained a value of R = 0.339 and R Square = 0.115 and a significance level of p = 0.000 (p < 0.005), meaning that there is a significant positive role for the variables of empathy and emotional intelligence to forgive women who experience sexual harassment.